A Novel EphA2 Inhibitor Exerts Beneficial Effects in PI-IBS in Vivo and in Vitro Models via Nrf2 and NF-κB Signaling Pathways - Zeng, Li; Li, Kaixue; Wei, Hong; Hu, Jingjing; Jiao, Lu; Yu, Shaoyong; Xiong, Ying (Frontiers in Pharmacology, 2018)
Though the detailed pathological mechanism of post-infectious irritable bowel syndrome (PI-IBS) remains unclear, accumulating evidence indicates that oxidative stress and inflammation are implicated in the process of PI-IBS. Oxidative stress and inflammation are regulated by Nrf2 and NF-κB signaling pathways, respectively. EphA2, a member of Eph receptor family, promotes oxidative stress and inflammatory responses via regulation of Nrf2 and NF-κB signaling pathways in various types of human diseases. Understanding the mechanisms by which EphA2 regulate oxidative stress and inflammation in PI-IBS is important for the development of new strategies to treat PI-IBS. However, the effects of ALW-II-41-27, a novel EphA2 inhibitor on PI-IBS and the underlying molecular mechanisms have never been studied. In the present study, we showed that ALW-II-41-27 decreased gastrointestinal motility and abdominal withdrawal reflex (AWR) scores, markedly reduced the levels of oxidative stress markers [4-hydroxy-2-nonenal (4-HNE), protein carbonyl, and 8-hydroxy-2-de-axyguanine (8-OHdG)] and proinflammatory cytokines (TNF-α, IL-6, IL-17, and ICAM-1), and remarkably increased the level of anti-inflammatory cytokine (IL-10) in serum and colon of Trichinella spiralis-infected mice. Moreover, ALW-II-41-27 was effective in suppressing oxidative stress and inflammation in LPS-treated NCM460 colonic cells. Treatment of ALW-II-41-27 reversed the activation of NF-κB and inactivation of Nrf2 in LPS-treated NCM460 cells. Importantly, these protective effects of ALW-II-41-27 were partially inhibited by EphA2 KO and abolished by EphA2 overexpression. In conclusion, EphA2 may represent a promising therapeutic target for patients with PI-IBS and ALW-II-41-27 might function as a novel therapeutic agent for PI-IBS.